Humor e história em mendigos : narrativas de Alphonsus de Guimaraens - Fernandes, Danielle Fardin (2024)
Alphonsus de Guimaraens published the book Mendigos in 1920, shortly before his death (in 1921). In the book, there are 44 chronicles and a poem. These are narratives that address multiple subjects, but have a very frequent resource, which is humor, in the broadest sense. This is because the humor he creates does not provoke easy laughter, but requires reflection and deciphering elements not always visible to the reader, especially the contemporary reader. The thesis proposes to examine a large part of these chronicles, analyzing them in the light of humor. Before, however, we make considerations about Symbolism (Brazilian and European) and the concept of humor, using in particular texts by Sigmund Freud, Henri Berg son, Vladimir Propp and Elias Thomé Saliba. The analysis of the chronicles brought to light the existential, philosophical and even epistemological conflict of the writer who, living in a hegemonically religious world, even more residing in the baroque environment of Minas Gerais, does not fail to criticize Christian values and characters, without, however, disconnect everything from the metaphysical imagination. The thesis seeks, then, to point out the emer gence of humor precisely in this in-between place where the fissure of faith allows humor to break out, in the form of laughter, irony, wits, mockery and even jokes